Enhanced synergistic catalysis of novel Ag2O/CuO nanosheets under visible light illumination for the photodecomposition of three dyes. Issue 2 (April 2021) - Akram, Naeem; Guo, Jia; Guo, Yuan; Kou, Yuli; Suleman, Humbul; Wang, Jide
Abstract: Visible-light photocatalysis is considered a good alternative for effluent degradation, resulting in eco-friendly biodegradable products. Semiconductors derived bimetallic nanocomposites have sufficient bandgap potential for efficient effluent treatment upon their exposure to the visible light. In this work, Ag2 O was deposited over CuO to improve the light captivating properties of the as-synthesized bimetallic catalyst. The bimetallic catalyst was studied for the photodegradation of three different azo dyes, by introducing persulfate as a sacrificial donor, under visible as well as sunlight irradiation. Novel leaf-like Ag2 O/CuO catalyst has efficiently degraded 100% Congo Red (CR), 99.9% Rhodamine-B (RhB), and 97% Methyl Orange (MO) dyes within 6 min, 15 min, and 20 min, respectively. Photodecomposition of all three dyes was studied at various pH solutions and the most efficient photodegradation was observed with a neutral pH solution. ESR and radical probe experiments were conducted to identify the active radical species and to reveal the reaction mechanism. SO4 − and HO radicals were the influential radicals during the photodegradation reaction. Notably, Ag2 O/CuO catalyst exhibited 100% photodegradation of Congo Red dye without the addition of persulfate within 8 min, a superior characteristic than the other known bimetallic catalysts. The developed catalyst is easily recyclable and offered just a 1–2% decrease in its photocatalytic performance, for all three dyes, even after 5 consecutive cycles. Thus, the reported catalyst can be a suitable alternative to expensive rare-earth derived bimetallic catalysts and has a potential application for the detoxification of various organic pollutants, at the field scale. Graphical Abstract: ga1 Highlights: Photodegradation of organic dyes via semiconductor derived bimetallic oxides. Novel Ag2 O/CuO nanosheets were prepared via a facile co-precipitation method. Photodegradation efficiency of the bimetallic oxide is 97–99.9% for all three dyes. Ag2 O/CuO showed excellent stability and reusability of catalyst. Mechanism for synergistic catalysis of Ag2 O/CuO nanosheets was elaborated.